Scedosporium apiospermum, an emerging pathogen in India: Case series and review of literature - Dabet Rynga; Malini R Capoor; Swati Varshney; Mayuresh Naik; V Gupta (Wolters Kluwer Medknow Publications, 2017)
Scedosporium apiospermum is a rare cause of infection but is increasingly being reported among immunocompromised individuals around the world. We report two cases of S. apiospermum, one of keratitis and the other of nasal polyp both from immunocompetent patients. The two cases were successfully treated with voriconazole. It is important to diagnose such infections as their antifungal susceptibility to amphotericin B is variable.